IMPLEMENTATION OF VISIONARY LEADERSHIP IN FORMING THE EXCELLENT POSITION OF THE INDONESIAN NATIONAL POLICE (POLRI) IN THE METROPOLITAN POLICE REGION - Muh. Mahdi Heaveny N.; Surya Nita; Yopik Gani (Transpublika Publisher, 2024)
The visionary leadership style focuses on school principals' ability to create a forward-thinking vision for the school, driving change and setting the organization's direction. This scientific article proposes implementing visionary leadership to shape the Indonesian National Police (Polri) excellence in the Jakarta Metropolitan Police. The study uses a qualitative approach with analytical descriptive to provide a detailed overview. Primary and secondary data, collected through observation, interviews, and document studies, are used. The author validates the data using triangulation techniques. The research findings reveal that visionary leadership is performance-oriented, with a focus on designing a future vision. It encompasses three characteristics: (1)